Oligometastatic Disease at Presentation or Recurrence for Nonsmall Cell Lung Cancer - Daniel R. Gomez; Yuzuru Niibe; Joe Y. Chang (Pulmonary Medicine)
Oligometastatic Non-Small Cell Lung Cancer (NSCLC) presents a unique opportunity for potential curative therapy. Improved cancer staging using PET/CT, MRI, and future cellular and molecular staging with circulating tumor cells and/or molecular markers will identify more patients with truly oligometastasis disease that will benefit from definitive local treatment. Recent development of noninvasive local ablative therapy such as stereotactic radiotherapy makes it possible to eradicate multiple local diseases with minimal side effect. Novel systemic therapy may also control systemic spread and therefore make it possible to improve survival by eliminating local diseases. More research, particularly prospective studies, is ideally randomized studies are needed to validate the concept of oligometastasis.